Constructing Utilitarianism : Montesquieu on Suttee in the Lettres persanes - Betts, Christopher J. (1997)
Constructing Utilitarianism : Montesquieu on Suttee in the Lettres persanes (1997) 27 mars 2010, par Betts, Christopher J. French Studies, 1997, vol. 51, n° 1, p. 19-29.
Keywords: exportSPIP